PENGEMBANGAN ALAT PERAGA KOTAK MITIGASI BENCANA SEBAGAI PENUNJANG PEMBELAJARAN KEBENCANAAN DI SEKOLAH DASAR - Ayub, Syahrial; Verawati, NNSP; Ardhuha, Jannatin; Zuhdi, Muhammad (Kappa Journal, 2020)
The purpose of this research is to develop a tool for disaster mitigation box as a support for learning disaster in elementary schools. This research uses the R&D approach according to Borg & Gall, which includes the step of development, pilot testing, and the final testing. In The development stage, resulted in seven aspects of the mitigation box namely a disaster poster, disaster impact poster, evacuation map, symbols for evacuation, newspaper clippings, disaster stories and songs about disasters. The seven aspects are declared very feasible to use in disaster learning. The trial phase is a limited trial. Limited trials were carried out 2 times to 32 students in grade III of SD Negeri 6 Mataram. In this limited trial it was stated that this disaster mitigation box was very suitable for learning. Disaster mitigation box testing phase is the stage to determine the effect of the use of disaster mitigation boxes to increase disaster awareness. Increased disaster awareness is determined based on the gain score. The results of the study concluded that the gain score for implementing the disaster mitigation box was 0.50 (medium). The development of the disaster mitigation box teaching aid received a good response from students by 80.80% and according to observers the learning went very well. The results of the research and validation test of learning development experts using disaster mitigation box props are worthy to be used as references in disaster learning.